Factors Related to University Students’ Motivation and Instruments for Its Evaluation: A Systematic Review - Sánchez-Bolívar, Lionel (2022)
Background. One of the most important factors in the incorporation to study a university degree in the educational performance and the professional future of university students is motivation. Purpose. This study aims to develop a systematic review of the literature that studies motivation in these students and determine the factors related to it and the instruments used to measure it. Method. For the research purpose, the method consisted in examining the terms motivation and university students (in Spanish and English) in the Web of Science and Scopus databases, selecting 66 articles reviewed between 2009 and 2019. These articles were selected according to two criteria: cross-sectional and quantitative studies with a pre-experimental or quasi-experimental design and sufficient statistical data to perform the analysis. Results. The scientific production in this field has an increasing trend. The studies have been conducted predominantly with students enrolled in different university degrees. The presence or absence of motivation corresponds to tendencies to procrastination. Conclusions. Therefore, it is necessary to highlight the importance of research and intervention in the university students’ motivation to improve their academic performance.